Evaluation of translucency of two types of glass-ceramics with different thickness: an in vitro study - Eladawy, Mostafa Ashraf; Ragab, Mostafa; Gamal, Monir; Azer, Amir; Ashour, Youssef; Taha, Mohamed (International Journal of Dental Materials, 2020)
Background: Veneered all-ceramic restorations are associated with a high incidence of chipping and veneer delamination from the inner core. Monolithic all-ceramic crowns facilitate the fabrication process and minimize residual stresses between core and veneer. A new material, zirconia-reinforced lithium silicate (ZRL), Celtra Duo was recently introduced for the fabrication of monolithic anterior crowns to overcome the aesthetic drawbacks of traditional zirconia and also to improve the strength of the lithium disilicate.Aim: This study aimed to evaluate and compare the translucency of CAD/CAM zirconia reinforced lithium disilicate ceramic and Lithium silicate glass-ceramic at a different thickness.Materials and Methods: CAD/CAM Lithium Silicate glass-ceramic (e.max CAD) and CAD/CAM ZLS Celtra Duo ceramic materials were used in the study. A total of forty Disc-shaped ceramic specimens (n=40), which comprises 20 from each ceramic material (n=20) were fabricated. The twenty specimens from each material group were divided into four subgroups with five specimens each (n=5) with a thickness of 1.0 mm, 1.2 mm, 1.5 mm and 2.0 mm, respectively. All the specimens were thermo-cycled to simulate one-year clinical service followed by analyzing the degree of translucency using spectrophotometer.   The obtained data were subjected to statistical analysis using the student t-test and post-hoc pair-wise comparisons.Results: A decrease in translucency with an increase in the thickness of the ceramic specimens was observed. Significant differences were observed between the ceramic materials except at 1.5 mm thickness (p=0.621).Conclusion: Both the ceramic materials displayed decreased in their translucency with the increase in the thickness. The glazed Celtra Duo has demonstrated relatively more translucency than e.max CAD ceramic at all thicknesses.